2010
DOI: 10.1016/j.jad.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Subregional hippocampal deformations in major depressive disorder

Abstract: Background Hippocampal atrophy is a well reported feature of major depressive disorder, although the evidence has been mixed. The present study sought to examine hippocampal volume and subregional morphology in patients with major depressive disorder, who were all medication-free and in an acute depressive episode of moderate severity. Methods Structural magnetic resonance imaging scans were acquired in 37 patients (mean age 42 years) and 37 age, gender and IQ-matched healthy individuals. Hippocampal volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 40 publications
(58 reference statements)
4
60
3
3
Order By: Relevance
“…However, our study did not detect significant differences in mean volumes, whereas MRI analyses in larger samples revealed deformations of shape in CA1 and CA2/3 subfields in the right posterior hippocampus in MDD patients (Cole et al 2010). Moreover, our current findings in MDD and BD show no similarities with our recent findings of decreased oligodendrocyte numbers in CA4 of the posterior hippocampus in patients with schizophrenia, which we obtained by using the same sectioning, histological staining technique and design-based stereology (Schmitt et al 2009).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, our study did not detect significant differences in mean volumes, whereas MRI analyses in larger samples revealed deformations of shape in CA1 and CA2/3 subfields in the right posterior hippocampus in MDD patients (Cole et al 2010). Moreover, our current findings in MDD and BD show no similarities with our recent findings of decreased oligodendrocyte numbers in CA4 of the posterior hippocampus in patients with schizophrenia, which we obtained by using the same sectioning, histological staining technique and design-based stereology (Schmitt et al 2009).…”
Section: Discussioncontrasting
confidence: 96%
“…These changes are already detectable during the first depressive episode (McEwen and Magarinos 2001) and may be less prominent or absent in phases of remission (Kempton et al 2011). Shape analysis of the hippocampus revealed deformations in the subiculum, the cornu ammonis subfield 1 (CA1) and cornu ammonis subfields 2/3 (CA2/3) in the tail of the right posterior hippocampus in patients with a first episode of depression (Cole et al 2010). In terms of anatomical connectivity, a voxel-wise meta-analysis of diffusion tensor imaging (DTI) studies in MDD confirmed a decreased fractional anisotropy in the white matter fascicles connecting the prefrontal cortex with cortical and subcortical areas such as the amygdala and hippocampus (Liao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses confirmed that in the aggregate the hippocampus is reduced in patients with major depression [66], [67], [72], [73]. Study results differ in localization of hippocampal volume loss with studies showing bilateral [11], [28], [49], [74][77], left unilateral [30], [78][80] and right unilateral [31], [81], [82] atrophy, which might be due to potential influencing factors like age, illness duration, recurrences, illness severity, comorbidity, medication or definition of hippocampal borders in MR images [83]. With respect to clinical variables influencing hippocampal volume, findings are inconsistent [67], [84].…”
Section: Discussionmentioning
confidence: 85%
“…However, to do this, we first investigated hippocampal functional changes following in vivo treatment with chronic nicotine and withdrawal, which may impact the efficacy of these drugs. To do this, evoked responses were recorded from ventral Electrical stimulation of the Schaffer collateral pathway (Figure 5a and b) results in robust activation of the CA1, a region of the hippocampus sensitive to stress-induced synaptic remodeling (Dalla et al, 2009;Joels et al, 2004Joels et al, , 2008McEwen, 2001;McEwen and Magarinos, 2001;Shors et al, 1997Shors et al, , 2001) and shown to be selectively affected in individuals with anxiety disorders (Cole et al, 2010). As shown in Figure 5ci and ii ( þ 10ms), responses evoked in the CA1 by Schaffer collateral stimulation were significantly increased following chronic administration of nicotine relative to saline controls.…”
Section: Alterations In Anxiety-like Behavioral Responses In the Nih mentioning
confidence: 99%